Pembelajaran Tematik-Integratif Sebagai Upaya Meningkatkan Keterampilan Abad ke-21 Siswa Sekolah Dasar - Maulida, Kamila Syifa (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research aims to explore the effectiveness of thematic-integrative learning in enhancing 21st-century skills among elementary school students. The research method involves the implementation of a thematic-integrative curriculum in core subjects such as language, mathematics, and science. Data were collected through classroom observations, teacher interviews, and student skill evaluations. The results show a significant improvement in students' critical thinking, creativity, collaboration, and communication skills. Thematic-integrative learning provides relevant and real-world contexts, motivating students to learn holistically. These findings support the concept that this approach can be effective in preparing students to meet the demands of 21st-century skills. The practical implications of this research emphasize the need for thematic curriculum integration to equip students with the necessary skills in the modern era.